Case Report: Non-negligible Epstein-Barr virus-associated posttransplant lymphoproliferative disorders in a lung transplant recipient - Hu, Juan; Yu, Yong-Wei; Han, Dong-Sheng; Li, Xue-Jie; Zhang, Yi-Qi; Cai, Hong-Liu; Xiao, Yong-Hong; Zheng, Xia (Frontiers in Immunology, 2023)
Background Posttransplant lymphoproliferative disorders (PTLDs) are uncommon but serious complications in patients following solid organ transplantation. Primary Epstein-Barr virus (EBV) infection is a risk factor for the development of PTLD, especially early-onset PTLD, in EBV-negative recipients. To date, however, there are no specific guidelines on the threshold of EBV-DNA load for therapeutic intervention, the source for measurement (e.g., blood, bronchoalveolar fluid), or the use of antiviral agents as prophylaxis for early PTLD prevention in EBV-mismatched patients. Methods The present study describes a 56-year-old male lung transplant recipient diagnosed with EBV-associated PTLD. Results This patient had a history of invasive fungal disease and Mucor and Aspergillus fumigatus infections in the early post-transplant period, necessitating antifungal therapy throughout the course of the disease. The patient was EBV-positive 15 days after transplantation, with lung CT showing multiple bilateral nodules of varying sizes beginning 98 days after transplantation. A lung biopsy showed PTLD, and next-generation sequencing (NGS) revealed EBV. This patient, however, did not receive any antiviral therapy for early PTLD prevention or any PTLD-related treatment. He died 204 days after lung transplantation. Conclusion The present study describes a lung transplant recipient who developed EBV-associated PTLD, a non-negligible disease, after solid organ transplantation. Monitoring EBV-DNA load is important, as a sudden increase may be a sensitive indicator of PTLD. An earlier diagnosis may increase the likelihood of successful treatment.